The use of dermoscope to differentiate Pityrosporum folliculitis and Acne vulgaris - Tanojo, Natalia; Anggraeni, Sylvia (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Both Pityrosporum folliculitis (PF) and Acne vulgaris (AV) are chronic inflammation of pilosebaceous follicle but with different etiology. The similar findings may lead to misdiagnosis that worsen symptoms, especially if PF is treated with antibiotics meant for AV. A simple KOH examination helps to differentiate PF and AV is not always readily available in clinical setting.Purpose: to find an alternative, practical tool to confirm the diagnose of PF and AV.Review: Dermoscope is a handheld microscope equipped with 10x magnification and a light source for microscopic visualization of the subcutaneous structures. The monomorphic lesions in PF appear as hypopigmented, round lesions with coiled/looped hair in the center. Dermoscope image of AV varies according its polymorphic manifestations. A non-inflammatory AV shows a yellow-brown blockage in the center while inflammatory AV is depicted as round, whitish lesions with thin brownish borders and erythematous marginal lesions. Pustular AV appears as raised lesions with indistinct borders and white or yellowish in the middle and surrounding reddish borders.Conclusion: Dermoscope help to see skin structures invisible to naked eyes and thus, help to diagnose PF and AV.